Utopia and Apocalypse - Apocalypse and Utopia : A view of Art in Germany 1910-1939. - Lynton, Norbert (London : Fischer Fine Art Limited, 1977)
Arnold, Karl ; Barlach, Ernst ; Baumeister, Willi ; Bayer, Herbert ; Beckmann, Max ; Campendonck, Heinrich ; Dix, Otto ; Feininger, Lyonel ; Grosz, George ; Heckel, Erich ; Hölzel, Adolf ; H¨ch, Hannah ; Itten, Johannes ; Jawlensky, Alexej von ; Kandinsky, Wassily ; Kirchner, Ernst Ludwig ; Klee, Paul ; Kokoschka, Oskar ; Kollwitz, Kathe ; Macke, August ; Marc, Franz ; Meidner, Ludwig ; Moholy-Nagy, Laszlo ; Müller, Otto ; Nolde, Emil ; Pechstein, Max Hermann ; Rohlfs, Christian ; Schlemmer, Oskar ; Schmidt-Rottluff, Karl ; Schwitters, Kurt ; Segal, Arthur ; Walter, Hans
Utopia and Apocalypse - Apocalypse and Utopia : A view of Art in Germany 1910-1939, Fischer Fine Art Limited, London, March - May 1977
Engels
boek